Sistemas de transferência de energia sem fio e de comunicação bluetooth para dispositivos implantáveis de aquisição de sinais - Magnaguagno, Jeferson (2022)
Wireless power transfer systems are commonly found in battery charging solutions for electronic devices such as smartphones and tablets. In medicine, they are essential in providing energy to implantable units or ingestible capsules. Inductive links with two or more coupled coils were widely used in energy transfer, but few studies consider the use of Helmholtz coils in monitoring capsules. Typically, data transfer between a capsule and an external reading device can occur through the inductive link, applying digital modulation techniques, or requiring a specific RF communication system. In both cases, the minimization of the capsule size may require the development of a microchip. However, given the high cost of manufacturing microchips on a small scale, other solutions may become feasible, such as using small microcontrollers with the built-in Bluetooth communication technology. This work presents the development of a prototype of a monitoring capsule with an inductive link formed by five coils, two of which are Helmholtz coils coupled to a set of three 3D-type coils in the capsule, and a module with a microcontroller implementing the Bluetooth Low Energy communication technology. In addition, a class E amplifier was developed to supply power to the link. Experiments were carried out to evaluate the energy received in the capsule and the efficiency, considering a separation distance between the transmitter coil and the capsule’s 3D coil set, ranging from 0 to 240 mm. As a result, the maximum power received in the capsule was 662.2 mW for the distance of 0 mm, while the efficiency reached 3.31 %. Up to 240 mm it was still possible to maintain the regulation of 3.3 VDC for the microcontroller, resulting in a power of 103.2 mW and an efficiency of approximately 0.5 %, even with changes in the orientation of the 3D coil set. The use of BLE technology made it possible to transfer data to a smartphone at a sampling frequency of 4 Hz, compatible with monitoring parameters such as temperature and stomach pH.